2009
DOI: 10.5194/cp-5-695-2009
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the roles of ocean circulation and biogeochemistry in governing ocean carbon-13 and atmospheric carbon dioxide at the last glacial maximum

Abstract: Abstract. We use a state-of-the-art ocean general circulation and biogeochemistry model to examine the impact of changes in ocean circulation and biogeochemistry in governing the change in ocean carbon-13 and atmospheric CO2 at the last glacial maximum (LGM). We examine 5 different realisations of the ocean's overturning circulation produced by a fully coupled atmosphere-ocean model under LGM forcing and suggested changes in the atmospheric deposition of iron and phytoplankton physiology at the LGM. Measured c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
126
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(152 citation statements)
references
References 40 publications
21
126
5
Order By: Relevance
“…This supports previous model studies, which have identified GHG variations as an important contributor to Pleistocene glacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;AbeOuchi et al, 2013). And the results emphasize how important it is to identify the mechanisms responsible for the orbitalscale modulation of atmospheric CO 2 concentrations (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Chikamoto et al, 2012;Menviel et al, 2012;Brovkin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports previous model studies, which have identified GHG variations as an important contributor to Pleistocene glacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;AbeOuchi et al, 2013). And the results emphasize how important it is to identify the mechanisms responsible for the orbitalscale modulation of atmospheric CO 2 concentrations (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Chikamoto et al, 2012;Menviel et al, 2012;Brovkin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While the changes of earth's orbital and tilt parameters and the resulting shortwave radiative forcing at the top of the atmosphere are well understood, the carbon cycle feedbacks that led to the reconstructed atmospheric CO 2 changes are subject to ongoing research (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Brovkin et al, 2012;Chikamoto et al, 2012;Menviel et al, 2012). It was demonstrated, however, that the carbon cycle feedbacks played an important role during the last deglaciation and the Quaternary Period (last ∼ 2.6 million years), amplifying glacial-interglacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;Abe-Ouchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Observations indicate that the deep glacial ocean was much saltier and colder than today (Adkins et al, 2002), thus more stratified in the abyss. Such a deep stratification has important impacts on the ocean's circulation and carbon cycle, as pointed out by climate models of different complexities (Toggweiler, 1999;Paillard and Parrenin, 2004;Köhler et al, 2005a;Bouttes et al, 2009;Tagliabue et al, 2009). In particular, deep stratification is required to reconcile δ 13 C Tagliabue et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such a deep stratification has important impacts on the ocean's circulation and carbon cycle, as pointed out by climate models of different complexities (Toggweiler, 1999;Paillard and Parrenin, 2004;Köhler et al, 2005a;Bouttes et al, 2009;Tagliabue et al, 2009). In particular, deep stratification is required to reconcile δ 13 C Tagliabue et al, 2009). However, only box models could significantly reduce atmospheric CO 2 when prescribing a reduced Southern ventilation (Watson and Garabato, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneer work of Joussaume et al (1984), many models are being equipped with δ 18 O, δD and also δ 17 O water isotopes, including land surface models Henderson-Sellers et al, 2006), regional atmospheric models (Sturm et al, 2010) general circulation models , for the coupled ocean-atmosphere GISS model; Lee et al, 2012, for NCAR CAM2;Tindall et al, 2009, for HadCM3;Risi et al, 2010, for LMDZ4;Werner et al, 2011, for ECHAM5wiso;Yoshimura et al, 2011, for IsoGSM;Dee et al, 2015) and intermediate-complexity climate models (Roche and Caley, 2013, for iLOVECLIM). Similarly, carbon stable isotopes are also implemented in a growing number of land surface and ocean components (e.g., Tagliabue et al, 2009;Menviel et al, 2012;Sternberg et al, 2009). These new functionalities of climate models open the possibility to directly comparing the proxies measured in natural archives with model output, with the double interest of improving the understanding of proxy records, and model evaluation.…”
Section: Introductionmentioning
confidence: 99%